EFFECT OF CS, OM, IBC, AND CV ON COMPANY GROWTH WITH PROFITABILITY AS MODERATING VARIABLES - Muhammad Fikri Ramadhan fikri; Yamasitha -; Deni Saputra; Fitri Indah Mayang Sari (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2023)
The purpose of this study was to examine the effect of capital structure, managerial ownership, independent board of commissioners and firm value on firm growth with profitability as a moderating variable used as an independent variable and capital structure (DER), managerial ownership (KM) , independent board of commissioners (DKI). and firm value (PBV) and firm growth (AG) were used as dependent variables. And one moderating variable is profitability (ROA). The data used are financial reports and annual reports from 2015 to 2019. The sample in this study is manufacturing companies listed on the Indonesia Stock Exchange as many as 42 companies. The results of this study indicate that capital structure (DER), managerial ownership (KM), has a negative and significant effect on company growth (AG).